Upaya Meningkatkan Hasil Belajar Geografi Materi Geografi Politik Melalui Media Audio Visual dan Small Group Discussion Di Kelas A/B STKIP PGRI Padang - Edi Suarto, M.Pd (STKIP Pesisir Selatan, 2016)
AbstractThe problems to be examined in this study is: Does the Audio Visual Media And Small GroupDiscussion can improve learning outcomes Geography class A / B STKIP PGRI Padang? The purpose of this action research was to determine the learning outcome geography through the Audio Visual Media And Small Group Discussion on Student class A/B STKIP PGRI Padang This study uses classroom action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this study is the Student class A/B STKIP PGRI Padang. The data obtained are kualitatif.Dari quantitative data and analysis results can be seen that through the Audio Visual Media And Small Group Discussion had a positive impact in improving student learning outcomes characterized by increased mastery learning students in each cycle, ie pre-cycle (52.63%), the first cycle (73.68%), the second cycle (86.84%).Keywords: Audio Visual Media And Small Group Discussion, learning outcomes, PoliticalGeography.